2019
DOI: 10.1038/s41598-019-51205-w
|View full text |Cite
|
Sign up to set email alerts
|

The MTH1 inhibitor TH588 is a microtubule-modulating agent that eliminates cancer cells by activating the mitotic surveillance pathway

Abstract: The mut-T homolog-1 (MTH1) inhibitor TH588 has shown promise in preclinical cancer studies but its targeting specificity has been questioned. Alternative mechanisms for the anti-cancer effects of TH588 have been suggested but the question remains unresolved. Here, we performed an unbiased CRISPR screen on human lung cancer cells to identify potential mechanisms behind the cytotoxic effect of TH588. The screen identified pathways and complexes involved in mitotic spindle regulation. Using immunofluorescence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
5
26
0
Order By: Relevance
“…Kawamura et al. 26 , 31 , 47 , 48 have suggested that TH287 and TH588 might display their antitumor activities through off-target effect by suppressing tubulin polymerization, whereas these inhibitors were subsequently proved to activate in a different manner as compared to anti-microtubule agent. Indeed, it was recently demonstrated that MTH1 could bind tubulin and promote the progression of mitosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kawamura et al. 26 , 31 , 47 , 48 have suggested that TH287 and TH588 might display their antitumor activities through off-target effect by suppressing tubulin polymerization, whereas these inhibitors were subsequently proved to activate in a different manner as compared to anti-microtubule agent. Indeed, it was recently demonstrated that MTH1 could bind tubulin and promote the progression of mitosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…S3). To uncover quantitative differences in the DNA damage response, we established dose-response curves for cisplatin and etoposide that activates p53 through ATM/ATR, and for TH588 that activates p53 though USP28 24 . There was no difference in IC50 values between ZNF148 knockout cells and controls in any of the tested cell lines (Fig.…”
Section: Zfp148 Binds To Clustered Cytosine-rich Dna Elements In Basamentioning
confidence: 99%
“…On top of the MTH1 inhibition, alternative mechanisms of TH588 have been reported as its anti-cancer effects including tubulin depolymerization and AKT signaling downregulation [ 32 , 33 ]. To confirm it, we investigated the spindle morphology of mitotic cells upon treatment of 5 and 10 µM of TH588.…”
Section: Resultsmentioning
confidence: 99%